Social network sites (SNS) an archetype of techno-social stress: A systematic review - January F. Naga; Ryan A. Ebardo (Heliyon)
Background: Social Networking Sites (SNS) are widely used platforms known for both their hedonic and social connectivity benefits. Although there is considerable interest in understanding how personal technostress affects individual well-being, a significant gap remains in the systematic exploration of this topic within the literature. Methods: This review systematically examined 41 empirical studies from Scopus and PubMed published between 2014 and 2023, following PRISMA guidelines, and assessed for methodological quality using the Mixed Method Appraisal Tool. Only English-language articles were considered to avoid translation complexities. Studies were categorized and coded using the Stressor-Strain-Outcome (SSO) model to examine demographic variations in stressor impacts and coping mechanisms. Results: The findings reveal a complex interplay of technological, behavioral-technological, and social stressors. Technological complexities often exacerbate social stressors like FoMO (Fear of Missing Out) and social overload, resulting in psychological (e.g., anxiety, depression), behavioral (e.g., reduced engagement), and physical strains (e.g., sleep disruptions). Demographic factors significantly influence stress responses, with younger users and women particularly affected. Key intervention strategies identified include digital detox practices, mindfulness techniques, and user-centered SNS design modifications. Conclusion: This review emphasizes the need for targeted approaches to mitigate SNS-induced technostress to foster balanced, health-oriented digital engagement. Future research should focus on developing comprehensive frameworks to address technostress impacts on diverse user groups better and support sustainable digital well-being practices.